CRISPR in 3D: Innovations in Disease Modelling and Personalized Medicine - Louis J Gautier (BioTechniques)
The CRISPR-Cas system of genetic engineering has had a significant impact on science and society since its advent in 2013. CRISPR integration with 3D culture systems such as organ-on-a-chips, as well as fast emerging commercial technologies, has encouraged translation of more complex pathophysiological modelling and personalized medicine.